Log house built by Christian Smith in 1780, on the Joseph Leinbach land. - Unknown (Forsyth County Public Library, 2008)
Oversize. Date unknown.
Log house built by Christian Smith in 1780, on the Joseph Leinbach land, 8 miles N. W. of Winston-Salem. The British army encamped here on its way from the Shallowford, on the Yadkin River, to Guilford Courthouse, Feb. 8, 1781.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth